N = 3 = 3-n?

N = 3 = 3-n?
Anonim

תשובה:

ראה הסבר …

הסבר:

שים לב שניתן להגדיר את הערך המוחלט כ:

# (x) = (x = "if" x> = 0), (-x "if" x <0):} # #

כמו כן, שים לב:

#n - 3 = - (3 - n) #

אם #n - 3 = 0 # לאחר מכן # 3 - n = 0 # you

#abs (n-3) = ABS (3-n) = 0 #

אם #n - 3> 0 # לאחר מכן # 3 - n <0 # you

#abs (n-3) = n-3 #

#abs (3-n) = - (3-n) = n-3 #

אם #n - 3 <0 # לאחר מכן # 3-n> 0 # you

#abs (n-3) = - (n-3) = 3-n #

#abs (3-n) = 3-n #

אז עבור כל הערכים הריאליים של # n #, יש לנו:

#abs (n-3) = ABS (3-n) #